Shareholder Value Creation: A Review of the Theoretical and Empirical Literature. (September 2018) - Venugopal, Merugu; Ravindar Reddy M.,; Bhanu Prakash Sharma G.,
The article attempts to study in detail the significance of shareholder value creation in the companies in emerging markets and reviews the research articles and studies available in categories such as importance, empirical evidence and drivers of shareholder value creation. The purpose of this article is to give an insight into shareholder value in the first section followed by the empirical evidence and drivers of the shareholder value. For this purpose of review, the article considers various studies made on shareholder value creation published by various recognised and other recognised sources. It is observed that shareholder value creation is the most important objective in this competitive business environment to maintain the long-term relationship with the investors. The empirical evidence attempts to prove that value-based measures outperform the traditional accounting measures. The article tries to investigate the need for finding the superior measure among the shareholder value performance measures and recommends the need for reviewing the traditional performance methods.